0
$\begingroup$

As in title $$\tan{\frac{a}{2}}\cdot \tan{\frac{b}{2}}\cdot \tan{\frac{c}{2}}\leq \frac{1}{3\sqrt{3}}$$whats more, is that this is acute triangle. I think it should be doable somehow with Jensen inequality, but thats the point where i am getting confused - how define necessary function, what to do further, any hints would be appreciated, thanks in advance

$\endgroup$
  • $\begingroup$ What is $tg$ ??? $\endgroup$ – achille hui Mar 3 '13 at 19:58
  • $\begingroup$ tangens? It is sin / cos $\endgroup$ – fdhd Mar 3 '13 at 19:59
  • 1
    $\begingroup$ tangent is usually denoted as $\tan(x)$, you can apply Jensen's inequality to $\log(\tan(x))$. Notice when $\theta$ is an acute angle, $\frac{\theta}{2} \in (0,\frac{\pi}{4})$. Since $\frac{d^2}{dx^2} \tan(x) < 0$ over $(0,\frac{\pi}{4})$, $\log(\tan(x))$ is a strictly concave there. $\endgroup$ – achille hui Mar 3 '13 at 20:09
  • $\begingroup$ but what shall i do with $\frac{1}{3\sqrt{3}}$? $\endgroup$ – fdhd Mar 4 '13 at 19:24
  • 1
    $\begingroup$ $a + b + c = \pi$ implies the "mean" of $x$ to go into R.H.S of Jensen's inequality is $\frac{\pi}{6}$ and $\tan(\frac{\pi}{6}) = \frac{1}{\sqrt{3}}$. $\endgroup$ – achille hui Mar 4 '13 at 19:38
5
$\begingroup$

Method 1 - Jensen's inequality.

If an angle $\theta$ is acute, then $\frac{\theta}{2} \in (0,\frac{\pi}{4})$. Over the interval $(0,\frac{\pi}{4})$, we have

$$0 < \tan(x) < 1 \implies \frac{d^2}{dx^2} \log(\tan x) = \tan(x)^2 - \frac{1}{\tan(x)^2} < 0.$$

This means $\log(\tan x)$ is a strictly concave function there. Apply Jensen's inequality to $\frac{a}{2}, \frac{b}{2}, \frac{c}{2}$ and notice $a + b + c = \pi$, we get:

$$\begin{align}\log(\tan\frac{a}{2}) + \log(\tan\frac{b}{2}) + \log(\tan\frac{c}{2}) \le 3\log(\tan\frac{\pi}{6})\\ \implies \tan\frac{a}{2} \tan\frac{b}{2}\tan\frac{c}{2} \le (\tan\frac{\pi}{6})^3 = (\frac{1}{\sqrt{3}})^3 = \frac{1}{3\sqrt{3}} \end{align}$$

Method 2 - G.M. $\le$ A.M. and angle addition formula.

Recall the 3 angle addition formula for tangent:

$$\tan(\alpha + \beta + \gamma) = \frac{\tan\alpha + \tan\beta + \tan\gamma - \tan\alpha\tan\beta\tan\gamma} {1 - (\tan\alpha\tan\beta + \tan\beta\tan\gamma + \tan\gamma\tan\alpha)}$$

Notice $a + b + c = \pi \implies \tan(\frac{a}{2}+\frac{b}{2}+\frac{c}{2}) = \tan\frac{\pi}{2} = \infty$, we have:

$$\tan\frac{a}{2}\tan\frac{b}{2} + \tan\frac{b}{2}\tan\frac{c}{2} + \tan\frac{c}{2}\tan\frac{a}{2} = 1\tag{*}$$

Now $\tan\frac{a}{2}, \tan\frac{b}{2}, \tan\frac{c}{2} > 0$. Apply G.M. $\le$ A.M. to numbers on L.H.S of $(*)$, we get:

$$ \left(\tan\frac{a}{2}\tan\frac{b}{2}\tan\frac{c}{2}\right)^{\frac23} \le \frac13 \;\;\implies\;\;\tan\frac{a}{2}\tan\frac{b}{2}\tan\frac{c}{2} \le \frac{1}{3\sqrt{3}} $$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.